L’aqueduc de l’Yzeron : nouvelles données sur le double siphon de Craponne (Métropole de Lyon) - David Baldassari (Gallia)
The restoration of the piers of the Yzeron aqueduct’s double siphon at Les Tourillons undertaken by the town of Craponne in 2019 provided an exceptional opportunity to carry out a study of the structure of this construction, the remains of which, despite their qualities, had remained inaccessible until now.The work was carried out in two phases. In the first phase, monitoring was conducted prior to the erection of scaffolding and the excavation of a trench to establish the stability of the foundation wall of the eastern pier. In the second phase, a building survey was carried out on the two piers. Meticulous studies of all the walls were conducted by means of a high-resolution laser scanning survey and manual drawings. These studies first helped to determine the techniques and processes used in the building of the structure. And secondly, they allowed us to investigate whether the two piers were constructed in phases. This is particularly significant considering the differences in their construction: the western shows hints of the starting points of vaults, while the eastern pier shows no sign of the presence of one of these arches.Both piers have foundations whose bases are between 0.70 and 0.92 m wider than the walls. The foundations are at 289.05 m NGF and 289.17 m NGF.The eastern pier is 11.97 m high and presents a square floor plan 4.37 m wide, though with slightly irregular angles. The second pier, located 2.63 m to the west, is 11.70 m high, 4.37 m wide and 3.73 m long. At a level of 6.60 m, this pier shows the starting point of two vaults. Above this, the width of the pier wall gradually tapers to 2.80 m.The corefill of the walls consists of dense masonry blocks. What distinguishes this particular building technique is several layers of stone sealed by a gneiss mortar. A macroscopic study of 10 samples was undertaken to analyse the mortar used in the construction of the piers and concluded that both piers were constructed at the same time. The walls, built using the opus vittatum technique, consist of mostly rectangular gneiss rubble, subsequently refined. The corners of the piers use longer stones laid flat using the stretching bond method. The alternating juxtaposition of the masonry reveals the aesthetic of angle clamping regardless of structural purpose. The joints, while mostly eroded, are dense and slightly protruding. From studies of better-preserved locations, the mortar seems to have been compacted using a round headed trowel. The eastern pier has a double layer of bricks 1.30 m above the foundation. The vaults of the western pier are made of concrete and supported by a wall that rises 1.87 m from its base. The main arches have disappeared.That being said, an existing nearby remnant of this aqueduct shows a preserved arch head where the stones have been tailored to measure up to 0.50 m in length.About a hundred putlock holes were identified on all faces of both piers. They have all been identified as scaffolding sockets. Their dimensions are generally around 14.40 m high and 12.80 cm wide. The depth is more variable and ranges from 0.25 to 0.79 m. Most of the putlock holes are perpendicular to the exterior walls but in rare instances they have a slight incline. The horizontal and vertical organisation is fairly similar. The eastern pier has seven levels of three putlock holes except the eroded north face which has two levels of putlock holes. The western pier has six levels mostly containing two putlock holes. However, three putlock holes are also visible on both the eastern and western faces of the piers immediately beneath the starting point of the arch and the upper parts of the elevation. The average gap between a pair of putlock holes is 1.66 m whereas the average gap between three holes at the same level is 1.32 m. The horizontal gap between the putlock holes averages 1.51 m, except in the case of the northern and southern faces of the western pier which is 1.81 m from the starting point of the arches.The placement of the putlock holes reveals the different methods and solutions used for the erection of the scaffolding needed to build the structure. The presence and the typology of the putlock holes, and their uniform vertical positioning, indicate that scaffolding was erected on different types of perches. The few disparities identified in the placement of the putlock holes may possibly reveal the use of a tilted scaffolding system.The C14 analysis of the charcoal extracted from the mortar from both piers reveals the correlation of dates ranging from 0 to 20 Calibrated AD.Two facts can be ascertained from analysis of the data arising from the building survey. Firstly, both piers were constructed in an identical manner with no difference in terms of the techniques and materials used, with the exception of the double layer of brick inserted in the eastern pier. Secondly, whilst it is undeniable that the western pier supported two vaults, the perfectly homogeneous masonry of the western face of the eastern vault could, in this state, have supported a vault. The structure of Les Tourillons consequently indicates several construction phases. However, the uniform use of materials and techniques would favour consistency in the construction process. The information gathered through this survey of the piers is insufficient to discern the purpose and detailed chronology of these phases of construction.